Lessons learnt from the MAGNET Malawian-German Hospital Partnership: the German perspective on contributions to patient care and capacity development - Florian Neuhann; Sandra Barteit (BMC, 2017)
Abstract Background Malawi is a low-income country with one of the highest HIV prevalence rates worldwide (Kendig et al., Trop Med Health 41:163-170, 2013). The health system depends largely on external funding. Official German development aid has supported health care in Malawi for many years (German Embassy Lilongwe, The German Development Cooperation in Malawi), including placing medical doctors in various departments of the Kamuzu Central Hospital (KCH) in Lilongwe. In 2008, a hospital partnership called MAGNET (Malawi German Networking for Capacity Building in Treatment, Training and Research at KCH) evolved as part of the German ESTHER network. The partnership was abruptly terminated in 2015. Methods We reviewed 35 partnership documents and conducted an online survey of partnership stakeholders to retrospectively assess the hospital partnership based on the Capacity WORKS model of the German Corporation for International Cooperation (GIZ). This model evaluates systems' management and implementation to understand and support the functioning of cooperation within societies. Based on this model, we considered the five success factors for cooperation management: (1) strategy, (2) cooperation, (3) steering, (4) processes, and (5) learning and innovation. In an online survey, we used an adapted version of the partnership evaluation tool by the Centers for Disease Control and Prevention (CDC). Results From 2008 to 2015, the MAGNET partnership contributed to capacity building and improved patient care in the KCH Medical Department through clinical care, technical support, teaching and trainings, and operations research based on mutually agreed upon objectives. The MAGNET partnership was implemented in three phases during which there were changes in leadership in the Medical Department and the hospital, contractual policies, funder priorities and the competing influences of other actors. Communication and follow up among partners worked best during phases when a German doctor was onsite. The partnership was judged as a positive driver for change and support within the Medical Department, but eventually failed to implement self-sustainable, robust processes within the partnership to cope with multiple changes and challenges. Conclusion The MAGNET partnership made a considerable contribution to patient care, continuous medical education and operations research at KCH, despite its abrupt termination. Changes in the institutional infrastructure, donor policy and interpersonal relations contributed to the loss of shared expectations and the end of the project. Institutional-hospital partnerships, like MAGNET, can make a valuable contribution to health care provision and hence a wider health agenda, provided there is a flexible, mutually agreed upon strategy, personal commitment, continuous communication and robust processes. However, partnership projects remain vulnerable to the influences of external actors and structures. Ministries of Health and donor agencies should appreciate the particular strength of hospital partnerships.